Observation of Large Surface Area Exfoliation in Hydrogen Implanted Ge. Issue 16 (8th July 2020) - Pathak, Ravi; Dadwal, Uday; Kapoor, Ashok K.; Singh, Rajendra
Abstract : Large surface area exfoliation of the hydrogen (H)‐implanted Ge is investigated in this work. H + ions with a fluence of 1 × 10 17  cm −2 are implanted in Ge samples at liquid nitrogen and room temperature (RT). The formation of surface blisters and craters is observed in the samples annealed between 300 and 450 °C after implantation. Interestingly, samples implanted at RT show large surface area exfoliation extending over several hundreds of micrometer region after annealing. Secondary ion mass spectroscopy (SIMS) and depth‐resolved Raman spectroscopy are used to characterize the depth profile of implanted H + ions and stress in the damage region, respectively. The formation of the damage band filled with extended planar defects in the form of nanocracks is observed using a cross‐sectional transmission electron microscope (TEM). The physical understanding of the H‐induced internal pressure and stress in the surface blisters/craters is carried out using Föppl–von Karman theory of thin plates. Abstract : Effect of implantation temperature is studied in H‐implanted Ge. Large surface area exfoliation is observed after annealing at 500 °C for 30 min for samples implanted at room temperature. Cross‐sectional transmission electron microscope shows the formation of 2D extended defects in the damage region. Analytical study reveals that the pressure inside blisters expands nanocracks, which results in large surface area exfoliation.